Giant left atrial myxoma causing acute ischemic stroke in a child - Hayato Ise; Natsuya Ishikawa; Sentaro Nakanishi; Hiroyuki Kamiya (Surgical Case Reports, 2018)
Abstract Ischemic stroke is uncommon in pediatric populations and is sometimes caused by cardiac myxoma. In such cases, neurological deficits initially present in ischemic stroke due to emboli or thrombi of the myxoma. Echocardiography is helpful to diagnose myxoma in a timely manner and allows urgent surgical resection of the myxoma. We report a successful case of myxoma in a 7-year-old boy who initially presented with left-sided hemiparesis.